Sekolah Islam Terpadu di Kabupaten Kepulauan Selayar Dengan Pendekatan Arsitektur Islam - Lukamanul Hakim; Aris Sakkar Dollah; Muhammad Syarif; Mursyid Mustafa; Siti Fuadillah A. Amin; Salmiah Zainuddin (Universitas Muslim Indonesia, 2022)
In the current era of globalization, the development of the times is very fast and fast, making a big influence on the world of education, including in the aspect of human needs. Based on the analysis, Selayar Islands Regency is a regency located in South Sulawesi Province, which has an area of ​​10,503.69 km² between land and sea areas with a population of 135,809 people. Geographically, Selayar is located at the tip of Sulawesi Island from the north and south, and is one of the 24 regencies or cities in the South-Sulawesi Province. The method used in this design is an Islamic architectural approach with the intention of giving awareness to the public that the importance of applying Islamic concepts in building and planning must certainly be far from being wasteful because it is contrary to Islamic values. The results of this design cover an area of ​​± 2.5 Ha, Building Basic Coefficient (KDB) 40%, Green Open Space (RTH) 60%. The building area is 5,500 m² classrooms, 190 m² practice rooms, 660 m² leadership and administration rooms, 1,760 m² support rooms and 2,200 m² parking, which will be presented in the form of two-dimensional drawings, site analysis, analysis of shapes to three dimensions and animation through shape exploration. The building is the Kaaba with its basic shape is a cube. This study concludes that the Integrated Islamic School with an Islamic architectural approach is equipped with Islamic icon designs on each building as its own attraction.